PEMBELAJARAN BILANGAN PECAHAN DI SEKOLAH DASAR: Systematic Literatue Review - Sujana, Ghina Zakiyyah (Papanda Journal of Mathematics and Science Research, 2022)
In elementary school there are fractions which are one of the mathematics materials taught to students. Fractional numbers are numbers that consist of two parts, namely the number as the numerator and the number as the denominator where the two parts of the number are separated by a slash symbol (/). The format for writing fractions is as follows: where "A" is the divisor/number and "B" is the divisor (Muchlis, A.N 2018). However, from several research results that have been carried out, it shows that students still have difficulty in learning the material of fractions. The research method chosen in this study is the SLR (Systematic Literature Review) method. Data collection was carried out by documenting and reviewing all articles related to fractional learning in the 2017–2020 period. The articles used in this study were 30 journal articles obtained from Google Schoolar, Sinta, and Garuda. This study aims to conduct a literature review of learning fractions in elementary schools. Based on this research, it was found that the learning model that is widely applied in learning fractions is the Mathematics Realistic Education learning model and the learning media used is folding paper learning media (Origami). By studying fractions using the Mathematics Realistic Education learning model and folding paper learning media (Origami) can improve student learning outcomes in elementary school.